Adequate Selection of a Therapeutic Site Enables Efficient Development of Collateral Vessels in Angiogenic Treatment With Bone Marrow Mononuclear Cells. Issue 9 (September 2015) - Nemoto, Masaru; Koyama, Hiroyuki; Nishiyama, Ayako; Shigematsu, Kunihiro; Miyata, Tetsuro; Watanabe, Toshiaki
Abstract : Background: Induction of angiogenic mechanisms to promote development of collateral vessels is considered promising for the treatment of peripheral arterial diseases. Collateral vessels generally develop from preexisting arteriolar connections, bypassing the diseased artery. We speculated that induction of angiogenic mechanisms should be directed to such arteriolar connections to achieve efficient collateral development. The aim of this study was to verify this hypothesis using autologous transplantation of bone marrow mononuclear cells in the rabbit model of chronic limb ischemia. Methods and Results: The left femoral artery was excised to induce limb ischemia in male rabbits. In this model, arteriolar connections in the left coccygeofemoral muscle tend to develop into collateral vessels, although this transformation is insufficient to alleviate the limb ischemia. In contrast, arteriolar connections in the closely located adductor muscle do not readily develop into collateral vessels. At 21 days after ischemia initiation, a sufficient number of automononuclear cells were selectively injected in the left coccygeofemoral muscle (coccygeo group) or left adductor muscle (adductor group). Evaluation of calf blood pressure ratios, blood flow in the left internal iliac artery, and angiographic scores at day 28 after injection revealed that collateral development and improvement of limb ischemia were significantly more efficient in the coccygeo group than in the adductor group. Morphometric analysis of the coccygeofemoral muscle at day 14 showed similar results. Conclusions: Specific delivery of mononuclear cells to the coccygeofemoral but not the adductor muscle effectively improves collateral circulation in the rabbit model of limb ischemia and suggests that adequate site selection can facilitate therapeutic angiogenesis.